2019
DOI: 10.1016/j.heliyon.2019.e01989
|View full text |Cite
|
Sign up to set email alerts
|

Potential application of herbs and spices and their effects in functional dairy products

Abstract: Herbs and spices come from different parts of the plant are used to impart an aroma and taste to food. Several herbs have therapeutic properties such as antioxidative, anti-inflammatory, antidiabetic, antihypertensive and antimicrobial activities. Therefore, fortification of dairy foods with herbs and spices could help to provide functional dairy products with nutritional and medicinal values. Also, herbs and spices are used to improve the appearance and attractiveness of fortified foods for consumers and to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
126
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(131 citation statements)
references
References 34 publications
2
126
0
3
Order By: Relevance
“…Generally, peanuts and peanut butter are elegant protein choices because they are cholesterol‐free and lesser in saturated fat than the protein of animal sources (Kris‐Etherton, Zhao, Binkoski, Coval, & Etherton, 2001). A clinical study indicates that part of the beneficial effect of peanuts and peanut butter may be due to their fatty acid composition, particularly when they substituting peanuts and peanut butter for saturated fat that can reduce the risk of heart disease by 45% moreover improved blood flow (El‐Sayed & Youssef, 2019; Hu & Stampfer, 1999). Heart‐health benefits may also come from nutrients in peanuts such as fiber, magnesium, and other bioactive compounds (Al‐Delaimy, Rimm, Willett, Stampfer, & Hu, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, peanuts and peanut butter are elegant protein choices because they are cholesterol‐free and lesser in saturated fat than the protein of animal sources (Kris‐Etherton, Zhao, Binkoski, Coval, & Etherton, 2001). A clinical study indicates that part of the beneficial effect of peanuts and peanut butter may be due to their fatty acid composition, particularly when they substituting peanuts and peanut butter for saturated fat that can reduce the risk of heart disease by 45% moreover improved blood flow (El‐Sayed & Youssef, 2019; Hu & Stampfer, 1999). Heart‐health benefits may also come from nutrients in peanuts such as fiber, magnesium, and other bioactive compounds (Al‐Delaimy, Rimm, Willett, Stampfer, & Hu, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Consumers are aware that spices have several medicinal properties, including anti‐inflammatory, anti‐microbiological, and antioxidant properties, which serves as encouragement to the food industry to add herbs and spices to dairy products, such as cheese, yogurt, ice cream, and butter (Alenisan, Alqattan, Tolbah, & Shori, 2017; Ansari & Kumar, 2012; El‐Sayed & Youssef, 2019; Embuscado, 2015), thus increasing their perceived healthiness. Several studies cited by El‐Sayed and Youssef (2019) and Embuscado (2015) demonstrated that the addition of spices improved the physicochemical and microbiological properties of the developed product. In the food industry, a current trend exists promoting foods without synthetic additives.…”
Section: Introductionmentioning
confidence: 99%
“…These polyphenols could be incorporated [234] within a film or coating applied to the food [235], which could release the antioxidant into the product or act on its surface, limiting the oxidative reactions of food components [236]. Aromatic herbs containing polyphenols have been traditionally used as healthy food ingredients [237][238][239][240] obtained through an aqueous extraction [241,242] process.…”
Section: Plant Extracts Incorporated As Antioxidants In Chitosan/starmentioning
confidence: 99%